Identification And Classification of MSMEs During The Covid-19 Pandemic In The DKI Jakarta - Amaliyah, Ria; David, Wahyudi (Program Studi Manajemen, 2021)
The Covid-19 pandemic that has occurred since March 2020 has caused a recession in the Indonesian economy. Unlike the economic crises in 1998 and 2008 in Indonesia, the economic crisis in 2020 due to the Covid-19 pandemic affected almost all sectors and threatened the existence of MSMEs. This study aims to determine the impact of the Covid-19 pandemic on MSMEs in DKI Jakarta, identify and classify MSMEs during the Covid-19 pandemic and provide alternative solutions and strategies for MSME actors in dealing with the economic crisis due to the Covid-19 pandemic. The study was conducted on MSMEs in DKI Jakarta with a total sample of 1,511 respondents. The research was conducted through qualitative and quantitative approaches with descriptive statistical data analysis techniques and SWOT analysis. The results showed as many as 83% of MSMEs experienced a decrease in business circulation, with the classification of a decrease in business circulation of up to 50% by 48%, and the remaining 35% experiencing a decrease in business circulation of more than 50%. As many as 83% of MSMEs experienced a decline in business circulation, which was dominated by micro-businesses in the trade, hotel, and restaurant sectors, with an average age of 0-5 years. The MSME recommendation strategy was prepared through a SWOT analysis and an in-depth assessment of internal and external factors referring to the MSME main recommendation strategy through a Cartesian diagram.